The Use of Modeling Tools to Better Evaluate the Packaging Benefice on Our Environment - Coffigniez, Fanny; Matar, Céline; Gaucel, Sébastien; Gontard, Nathalie; Guilbert, Stéphane; Guillard, Valérie (Frontiers in Sustainable Food Systems, 2021)
Packaging play a key role on food quality preservation and shelf-life increase. Even if the link between shelf life and food loss has not yet clearly been formalized, it is generally observed that a well-designed packaging contributes to reduce food loss and waste (FLW) and thus the corresponding useless negative impact that producing and distributing uneaten or inedible food has on our environment and economy. In order to anticipate the usage benefit of a given packaging, decision making tools are needed to be developed. While some authors’ separately showed the importance of shelf life model, FLW prediction model and Life Cycle Analysis, so far no connection was really made between them. In this context, this paper aims to analyze the different mathematical modelling approaches proposed in the available scientific literature, from the prediction of food shelf life gain thanks to well-designed packaging to the environmental benefice due to the decrease of FLW. The article presents a review of 29 models developed on this thematic during the last two decades. The analyzed models were split in three categories: (1) the food shelf life models, (2) the models linking shelf life to FLW and (3) the Life Cycle Analysis including direct (production, processing and end of life) and indirect (FLW) packaging environmental impacts. In one hand, the review showed that if many predicting approaches were conducted to assess food shelf life, only few of them were enough mechanistic (by coupling mass transfer to food deterioration) to be used in other conditions than the ones initially studied. Moreover, the consumers’ practices and believes being strongly influent on the quantity of food waste at household, it should be more systematically integrated in the FLW estimation for a fairer evaluation. On the other hand, this review highlighted that even if indirect environmental benefit of packaging, e.g. through FLW decrease, is more and more integrated in life cycle analyses of the food packaging system, most of studies were only based on rough estimation and not on real quantification of the FLW reduction obtained thanks to the well-designed packaging.